Ultrafast exciton relaxation dynamics in silicon quantum dots - Cimpean, Carla Ramona; Groenewegen, Vincent; Kuntermann, Volker; Sommer, Anja; Kryschi, Carola (Laser & Photonics Reviews, 2009)
The photoluminescence properties of silicon quantum dots may be tailored by surface states via efficient coupling to resonant bulk states. Therefore various wet-chemistry procedures were developed to fabricate silicon quantum dots with adjustable sizes and surface properties. While the energy gap of the Si core is tuned by the size, resonant electronic surface states may be attained by varying the structure and chemical composition of the grafting. The strength of electronic couplings between surface and bulk states determines the timescale of both photo-induced electron transfer from excited surface states to conduction band states and capture of conduction band electrons by surface states. Whereas the origin of photoluminescence and therewith the quantum dot size distribution may be elucidated by stationary luminescence spectroscopy, ultrafast optical spectroscopy techniques, for instance the femtosecond transient absorption spectroscopy, allow to monitor photo-induced electron transfer between surface and bulk states and carrier trapping on the subpicosecond timescale. © 2009 by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Silicon quantum dots; photoluminescence; thermal hydrosilylation; femtosecond spectroscopy; photo-induced electron transfe